Star Performances: Ed Roberts on the Speaking Circuit, 1983-1995 - Danforth, Scot (Disability Studies Quarterly, 2020)
This article uses historical research methods to explore noted disability rights leader Ed Roberts' performances on the speaker circuit between 1983, when he left his position as director of the California Department of Rehabilitation, and his death in 1995. This article examines how he managed his performed identity, his self as presented on stage, in order to be a disability star. Using his own life story as a poignant example, he narrated an autobiography of how a paralyzed man could live a vigorous, successful, indeed a joyful life. His personal stories communicated his lived experiences of battling discrimination and stereotypes. Roberts skillfully and strategically marshalled his own growing celebrity as the most prominent disabled American while he promoted the cause of civil rights for disabled people.